The Influence of Metformin to the Transcriptional Activity of the mtor and FOX3 Genes in Parapancreatic Adipose Tissue of Streptozotocin-Induced Diabetic Rats - Putilin, D. A.; Evchenk, S. Y.; Fedoniuk, L. Y.; Tokarskyy, O. S.; Kamyshny, O. M.; Migenko, L. M.; Andreychyn, S. M.; Hanberher, I.I.; Bezruk, T. O.; Путілін, Денис Анатолійович (My University, 2020)
The mammalian target of rapamycin is not only a central regulator of lipid metabolism that controls the processes of adipogenesis and lipolysis but also a regulator of the immunometabolism of immune cells that infiltrate adipose tissue. In turn, the level of progression of diabetes is significantly influenced by the Treg subpopulation, the complexity and heterogeneity of which is confirmed by the detection of numerous tissue-specific Tregs, including the so-called VAT Tregs (visceral adipose tissue CD4+Foxp3+ regulatory T cells). Therefore, the purpose of the study was to determine the mRNA expression levels of mTOR, Foxp3, IL1β, and IL17A genes in rat parapancreatic adipose tissue with experimental streptozotocin-induced diabetes mellitus, with or without metformin administration. The experiments were performed on male Wistar rats with induced diabetes as a result of streptozotocin administration. Molecular genetic studies were performed using real-time reverse transcription-polymerase chain reaction. The development of diabetes caused transcriptional activation of the mammalian target of rapamycin protein kinase gene, as well as increased mRNA expression of the pro-inflammatory cytokines IL1β and IL17A, but did not affect Foxp3 mRNA expression. The intervention with metformin in diabetic rats inhibited the mammalian target of rapamycin mRNA expression and caused an increase in the transcriptional activity of the Foxp3 gene in parapancreatic adipose tissue.
Keywords: diabetes mellitus; streptozotocin; rat model; adipose tissue; mTOR; Foxp3; IL1β; IL17A